Modulated structures in the ANNNI model with an external magnetic ﬁeld near criticality - Gonchar, N.S.; Hajduk, H.G. (Condensed Matter Physics, 1999)
Conditions for a phase transition from the paramagnetic state to the modulated structure are found in a class of anisotropic Ising models with an
external magnetic ﬁeld. The critical value of the external magnetic ﬁeld is
obtained. Branching equations are derived and small branching theorems
are proven for commensurate and incommensurate conﬁgurations. Знайдено умови фазового переходу із парамагнітного стану до модульованої структури в класі анізотропних моделей Ізінга з зовнішнім
магнітним полем. Обчислено значення критичного магнітного поля.
Отримані рівняння галуження та доведені теореми про малі галуження для співмірних та неспівмірних конфігурацій.